Community Behavior in Artificial Intelligence-Based Waste Management - Sanny Edinov; Rezki Fauzi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The community is not yet aware that proper and correct waste management is the main capital in waste management. It is hoped that the community will improve their behavior and be used as a guide by the local government regarding what steps to take in the future to be more synergized with the community in managing waste. The people who have been tested are seen from recent education, discipline, and environmental knowledge, with a total sample of 100 people. The study used questionnaires and interviews as data collection tools. The data that has been obtained is analyzed by testing the criteria used is the Rough set. The results of the extracted criteria produce 9 varied general rules, which can produce solutions and steps forward as supporting success in creating a clean environment from waste